Community Participation in Public Schools : Impact of Information Campaigns in Three Indian States - Pandey, Priyanka; Goyal, Sangeeta; Sundararaman, Venkatesh (2012)
This study evaluates the impact of a community-based information campaign on school performance from a cluster randomized control trial in 610 villages. The campaign consisted of eight or nine public meetings in each of 340 treatment villages across three Indian states to disseminate information to the community about its state-mandated roles and responsibilities in school management. No intervention took place in control villages. At baseline there are no significant differences in school outcomes. This paper reports on the first follow up survey that took place two to four months after the intervention. We find that providing information through a structured campaign to communities had a positive impact in all three states. However, there are differences across states in where the impact occurs. The most notable impacts occurred on teacher effort, while impacts on learning were more modest. Some improvements also occurred in the delivery of benefits entitled to students (stipend, uniform, and mid-day meal) and in process variables such as community participation in each of the three states. Future research needs to examine whether there is a systematic increase in learning when the impact is measured over a longer time period and whether a campaign sustained over longer duration generates greater impact on school outcomes.